Students' Physics Problem-Solving Skills Using a Problem-Based Learning Model Assisted by Interactive PowerPoint - Adwan, Huriyah Amani; Harjono, Ahmad; Sutrio, Sutrio; ‘Ardhuha, Jannatin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This study aims to analyze the effect of a problem-based learning model assisted by interactive PowerPoint on students' physics problem-solving skills. The method used is a quasi-experiment with a non-equivalent control group design. The population of this study consists of all 11th-grade students at MAN 2 Mataram. The research sample consists of 21 students from class XI IPA 2 as the control group and 20 students from class XI IPA 3 as the experimental group, selected using purposive sampling. The research instrument used was a problem-solving ability test in the form of an essay. The results showed that the experimental class using the problem-based learning model assisted by interactive PowerPoint had a higher average final score of 84.12 compared to the control class, which had a score of 71.03 using a conventional learning model. Hypothesis testing obtained a sig. (2-tailed) value of 0.008 < 0.05, meaning that Ho is rejected and Ha is accepted. The conclusion is that the problem-based learning model assisted by interactive PowerPoint is effective in improving students' physics problem-solving skills.